Ranma 1/2. Vol. 12 - Takahashi, Rumiko, 1957- (Viz graphic novel, 2004)
Follows the adventures of half-boy, half-girl martial artist Ranma, whose transforming gender problems began at the Accursed Springs in China when he became cursed to turn into a girl when splashed with cold water, and back into a boy with hot water.